2002
DOI: 10.4319/lo.2002.47.2.0527
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nutrients and herbivory on competition between a hard coral (Poritescylindrica) and a brown alga (Lobophora variegata)

Abstract: Coral reef degradation often involves a phase shift from coral-to macroalgal-dominated reefs. Declining levels of herbivory or increasing supply of nutrients have both been suggested as a cause of increased algal abundance and consequent competitive overgrowth of corals. However, explicit demonstration of the processes involved and their relative strengths requires simultaneous tests of all three factors: competition, herbivory, and nutrient effects. We experimentally tested the factorial effects of nutrients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
2
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 33 publications
5
106
2
5
Order By: Relevance
“…Monitoring has shown that between 2003 and 2007, mean biomass of scarid parrotfish on Bonaire's reefs steadily declined from 7000 to 4000 g 100 m −2 (Alvarado et al 2007), and a 2006 nutrient survey suggests that Bonaire's reefs are at or beyond the threshold of nutrient pollution (Wieggers 2007). Effects of nutrient enrichment and reduced herbivory interact (Scheffer et al 2001, Jompa and McCook 2002, Littler and Littler 2007 and may operate synergistically to alter communities (Scheffer et al 2001). Once chronic human impacts have undermined resilience, pulses of mortality, such as that caused by a hurricane, can trigger a transition to macroalgal dominance (Littler and Littler 2007, Scheffer et al 2008, Hughes et al 2010) and increased abundance of other life forms such as soft corals and sponges (Norström et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring has shown that between 2003 and 2007, mean biomass of scarid parrotfish on Bonaire's reefs steadily declined from 7000 to 4000 g 100 m −2 (Alvarado et al 2007), and a 2006 nutrient survey suggests that Bonaire's reefs are at or beyond the threshold of nutrient pollution (Wieggers 2007). Effects of nutrient enrichment and reduced herbivory interact (Scheffer et al 2001, Jompa and McCook 2002, Littler and Littler 2007 and may operate synergistically to alter communities (Scheffer et al 2001). Once chronic human impacts have undermined resilience, pulses of mortality, such as that caused by a hurricane, can trigger a transition to macroalgal dominance (Littler and Littler 2007, Scheffer et al 2008, Hughes et al 2010) and increased abundance of other life forms such as soft corals and sponges (Norström et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In these field experiments, we used the corals P. porites (Caribbean Panama) and P. cylindrica (Fiji) because this is a pan-tropical genus common to both sites and used in other investigations of coral-seaweed competition (8,(17)(18)(19)22). The seaweeds we used were (i) common-to-abundant on these Poritid-dominated reefs, (ii) observed in contact with corals, and (iii) representative of a range of taxonomic and morphological forms.…”
Section: Methodsmentioning
confidence: 99%
“…In the Caribbean, average cover of hard corals has declined by ∌80% in the last 3 decades (5) and more than 30% of the world's coral species face elevated risk of extinction (6). Monitoring (7), field experiments (8)(9)(10), and a meta-analysis (11) all indicate that herbivory is critical in preventing seaweed replacement of corals. However, the extent to which seaweeds drive these shifts by outcompeting adult corals in the absence of herbivory, or proliferate only after coral mortality is triggered by other causes (such as disease or bleaching) is debated (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Many studies of coral-algal competition following a disturbance have focused on areas exposed to terrestrial runoff in the form of nutrients, pollutants and sediments (McCook 2001, Jompa and McCook 2002, Nugues and Roberts 2003, Birrell et al 2005, Haas et al 2009). Sedimentation in particular is considered a major cause of coral reef degradation through direct effects on coral reproduction, settlement and recruitment (Rogers 1990, Gilmour 1999, Wilkinson 2000, Fabricius 2005.…”
Section: Introductionmentioning
confidence: 99%